Testing vaccines in pediatric research subjects - Jacobson, Robert M. (2009)
Past difficulties encountered in pediatric vaccine research have positively influenced the development of modern regulations of human subjects’ research. These regulations permit pediatric research but impose special restrictions on the types of studies to which children may participate, and these restrictions have important implications for modern vaccine trials. These ethical issues pose real but surmountable concerns. Considerations also include the use of placebos, critical for trial design but an impediment to parental permission. Recent pediatric vaccine studies illustrate practical alternatives to placebos that preserve allocation concealment and blinding yet obtain parental support. Vaccine researchers must consider the role parents play, not just in giving formal permission for their children’s participation, but also for their roles in active recruitment, successful retention, and data acquisition. Studies of parents’ attitudes do identify consistencies among motivating forces that drive parents to participate or refuse their children’s participation. These studies should influence how we design and execute pediatric vaccine trials. Finally, ethical considerations and current regulations raise certain issues concerning the remuneration of the research volunteer when that volunteer is a child. The published literature illustrates wide variation in practice. Better understanding of the restrictions in pediatric research, the use of placebos, the attitude of parents, and the concerns with remuneration can better equip the vaccine researcher in pursuing successful studies in children.